The Role of Responsibility in Improving Mastery of Islamic Religious Education Material Moderated by Students' Disciplinary Behavior at the High School Level - Fikri, Muhamad; Madjid, Abd. (Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze the influence of responsibility on the mastery of Islamic Religious Education (PAI) material and to examine the role of disciplined behavior as a moderating variable in strengthening this relationship among high school students. This study uses a quantitative approach with a correlational design and explanatory survey method. The research was conducted through several stages, namely problem identification, literature review, variable determination and instrument adaptation, questionnaire distribution, data examination, outer model evaluation, inner model evaluation, and hypothesis testing. The research sample consisted of 56 high school students in the Yogyakarta region, selected using purposive sampling. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3. The research results show that discipline behavior has a positive and significant effect on the mastery of PAI material (0.503; t = 3.806; p = 0.000), while responsibility does not have a significant direct effect on the mastery of PAI material (0.171; t = 0.910; p = 0.363). Responsibility has a positive and significant effect on discipline behavior (0.715; t = 8.723; p = 0.000). Additionally, the interaction between responsibility and discipline behavior has a positive and significant effect on the mastery of PAI material (0.360; t = 3.678; p = 0.000), indicating that discipline behavior strengthens the influence of responsibility on students' mastery of PAI material. The research results show that disciplined behavior strengthens the relationship between responsibility and mastery of PAI material. This emphasizes that mastery of PAI material is not only determined by cognitive ability but also by the embodiment of responsibility in orderly and consistent learning behavior. PAI learning needs to emphasize the instillation of values and the formation of disciplined behavior.